Accounting for temporal variation of electricity production and consumption in the LCA of an energy-efficient house. (1st February 2016) - Roux, Charlotte; Schalbart, Patrick; Peuportier, Bruno
Abstract: The development of on-site renewable energy production and demand management in buildings calls for a deeper understanding of the interaction between building operation and the electricity grid. Electricity consumption in buildings varies in terms of seasons (heating and cooling), day of the week (professional activities) and hour of the day, which is also the case of on-site electricity production (e.g. photovoltaic systems). Centralised electricity production varies as well according to the demand (e.g. during peak hours). This research aims at improving the evaluation of potential environmental impacts of an energy efficient house attributable to electricity consumption and production by taking into account the temporal variation of the electricity production. Electricity end-uses and on-site electricity production were evaluated on an hourly basis in the case of an energy-efficient house. Another objective was to investigate the sources of errors in the assessment. Life cycle assessment was used to evaluate potential environmental impacts based on electricity production data for the year 2013 in France. Results were compared using an annual average electricity supply mix versus hourly data. This case study demonstrates that the use of an annual average mix instead of hourly mix data can lead to underestimation of potential impacts up to 39% for Abiotic Depletion Potential (ADP) and 36% for Global warming potential (GWP) when combining all end-uses. Increase of GWP and ADP when using hourly mix data is mainly explained by higher share of coal and gas power plant in the electricity mix in winter. This coincides with a higher electricity consumption of the studied house in this season due to space heating, electric back-up of the solar water heating system and a lower onsite production (photovoltaic system). Graphical abstract: Highlights: The use of a static average electricity mix is common in building LCA. We propose a dynamic evaluation based on 2013 hour-by-hour power generation data. We compare the two assessments in the case of a low-energy house. Using an average electricity mix can lead to errors in LCA of buildings.